Numerical Investigation of Wellbore Stability in Deepwater Shallow Sediments. (15th March 2021) - Liu, Wei; Lin, Hai; Liu, Hailong; Luo, Chao; Wang, Guiping; Deng, Jingen
Abstract : An elaborate poro-elastoplastic numerical model has been developed in this paper to explore the stability characteristics of wellbore in shallow sediments of deepwater oil/gas wells. The combined Drucker-Prager/cap plasticity model is employed to characterize the mechanical behavior of the weakly consolidated or unconsolidated shallow sediments, by which both plastic compaction deformation and plastic shear deformation can be considered. Possible penetration of drilling fluid into the formation and its coupling to deformation have also been accounted for in the model. Using this model, deformation, stress evolution, and failure characteristics of the formation around the wellbore are analyzed in detail. Results presented in this paper demonstrate the necessity of considering the plastic compaction capability of the formation during the wellbore stability analysis of shallow sediments in deepwater. For mud pressures lower than the in situ horizontal stress, excessive wellbore shrinkage may occur if the mud pressure is too low, which, however, can be effectively mitigated through properly increasing the mud pressure even fluid penetration into the near-wellbore region may occur. It is also evidenced that, if penetration of drilling fluid into the formation is prevented, fracturing of the wellbore will not occur even the mud pressure is very high. Instead, the wellbore will expand substantially due to plastic compaction, and the deformed wellbore radius could be several times larger than the original value. However, if drilling fluid can penetrate into the formation, high pore pressure will develop within the near-wellbore region, resulting in tensile hoop stress at the wellbore and thus fracturing of the wellbore along the radial direction. The numerical results and implications in this paper are anticipated to be beneficial for the drilling operation in the shallow portion of deepwater oil/gas wells.